A surface hardening and corrosion-resistant process for hydraulic cylinders

Through the process of hardening the surface of the hydraulic cylinder and applying a corrosion-resistant coating, the corrosion and wear problems of hydraulic cylinders in harsh environments are solved, and the effect of improving hardness, wear resistance and corrosion resistance is achieved.

CN119060618BActive Publication Date: 2025-04-01JINING YITONG HYDRAULIC PARTS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411197378.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-04-01
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

Hydraulic cylinders are easily corroded in harsh environments and are easily scratched by external impacts, resulting in surface wear. The prior art is difficult to effectively solve these problems.

Method used

A process is adopted to first harden the surface of the hydraulic cylinder, and the hardness and wear resistance are improved by mixing boron supply agents, rare earth compounds, graphite and boron nitride and other substances; then the photothermal double curing epoxy resin material and superhydrophobic polyurethane coating are coated to form a tight mesh structure through photocuring and thermal curing to improve corrosion resistance.

Benefits of technology

The hardness and wear resistance of the hydraulic cylinder surface are significantly improved, and by forming a hydrophobic coating, it significantly improves its corrosion resistance in a corrosive environment and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of metal surface treatment, and in particular to a surface hardening and corrosion-resistant process for a hydraulic cylinder. The present invention provides the following schemes: (1) a boron supply agent, a rare earth compound, a filler, and a catalyzer are mixed and ball-milled to obtain a surface hardener, and the surface hardening agent is used for the surface hardening treatment of the hydraulic cylinder; (2) 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methacrylic acid are used as raw materials to react to obtain a photothermal dual-curing epoxy resin material; (3) polyurethane prepolymers are terminated with glycidol to obtain epoxy polyurethane; polyurethane prepolymers are terminated with hydroxyethyl acrylate, and 1,1,3,3-tetramethyldisiloxane is used as a chain extender to obtain a double-bond terminated polyurethane; epoxy polyurethane, double-bond terminated polyurethane, and hydrophobically modified silica are mixed to obtain a super-hydrophobic polyurethane coating; (4) the photothermal dual-curing epoxy resin material and the super-hydrophobic polyurethane coating are sequentially applied to the surface of the hydraulic cylinder after hardening treatment to form a corrosion-resistant coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface treatment, in particular to a surface hardening and corrosion-resistant process for a hydraulic oil cylinder. Background Art

[0002] A hydraulic cylinder is a hydraulic actuator that converts hydraulic energy into mechanical energy and performs linear reciprocating motion (or swinging motion). In the process of using a hydraulic cylinder to achieve reciprocating motion, a deceleration device can be eliminated, and since there is no transmission gap, its motion is more stable, so it is widely used in the hydraulic systems of various machines.

[0003] When using hydraulic cylinders, since most of them work in harsh environments, many parts are easily corroded, so it is necessary to pay attention to rust prevention. In addition to environmental factors, hydraulic cylinders may also be scratched by external impacts. At this time, its surface hardness should be increased to ensure that the hydraulic cylinder is in good condition and prevent wear during operation. Therefore, it is very necessary to provide a surface hardening and corrosion-resistant process for hydraulic cylinders to improve their good performance in practical applications. Summary of the invention

[0004] The purpose of the present invention is to provide a surface hardening and corrosion-resistant process for a hydraulic cylinder to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a surface hardening and corrosion resistance process of a hydraulic cylinder, comprising the following steps:

[0006] Step 1:

[0007] S11: heating 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane to 80-90°C, mixing a phase transfer catalyst benzyltriethylammonium chloride, a polymerization inhibitor p-hydroxyanisole, and α-methylacrylic acid, and adding the mixture to 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, heating the mixture to 95-100°C and reacting the mixture at a constant temperature for 2-3 hours to obtain an acrylic acid-modified epoxy resin;

[0008] S12: mixing an acrylic modified epoxy resin, an epoxy diluent, a free radical active diluent, a photoinitiator, and an epoxy curing agent to obtain a light-heat dual-curing epoxy resin material;

[0009] Step 2:

[0010] S21: dispersing nano-silica in anhydrous ethanol, adding deionized water and ammonia water, stirring and adding dodecyltriethoxysilane, reacting at 70-80° C. for 6-8 hours, filtering and washing by centrifugation with anhydrous ethanol, and vacuum drying to obtain hydrophobically modified silica;

[0011] S22: Mix polyethylene glycol 2000 and isophorone diisocyanate, use dibutyltin dilaurate as a catalyst, raise the temperature to 70-80° C., and keep the temperature for reaction for 2-3 hours to obtain an isocyanate-terminated polyurethane prepolymer;

[0012] S23: Mixing a polyurethane prepolymer with glycidol according to the isocyanate group, using dibutyltin dilaurate as a catalyst, heating to 60-70°C for reaction for 1-2 hours to obtain an epoxy-terminated polyurethane; mixing a polyurethane prepolymer with hydroxyethyl acrylate according to the ratio of isocyanate group to hydroxyl group of 1:1, using dibutyltin dilaurate as a catalyst and p-hydroxyanisole as a polymerization inhibitor, heating to 60-70°C for reaction for 1-2 hours, adding 1,1,3,3-tetramethyldisiloxane while keeping the temperature, using chloroplatinic acid / isopropanol solution as a catalyst, adding acetone during the reaction to adjust the viscosity, reacting for 8-10 hours, and removing the acetone by vacuum distillation to obtain a double-bond-terminated polyurethane;

[0013] S24: mixing epoxy-terminated polyurethane and double-bond-terminated polyurethane in a mass ratio of 1:(4-9), adding deionized water for emulsification to obtain a composite polyurethane emulsion with a solid content of 25-30%; adding 3-5 parts of hydrophobically modified silica to 100 parts of the composite polyurethane emulsion, and mixing to obtain a super-hydrophobic polyurethane coating;

[0014] Step 3:

[0015] S31: vacuum-packing the boron supply agent, the rare earth compound, and the filler, ball-milling the mixed powders, adding the infiltration agent, vacuum-packing again, and continuing the ball-milling to obtain the surface hardener;

[0016] S32: Use oxalic acid solution to remove rust and oil from the surface of the hydraulic cylinder, wash and dry it, put it into a surface hardener for heating and infiltration, heat it to 600~650℃ and keep it for 1~2h, continue to heat it to 950~980℃ and keep it for 3~5h; cool it to 25~30℃, then quench it at 600~650℃, and temper it at 200~220℃ to obtain a surface hardened hydraulic cylinder;

[0017] S33: Apply the photothermal dual-curing epoxy resin material to the surface of the surface-hardened hydraulic cylinder with a coating thickness of 150-200 μm; then apply the super-hydrophobic polyurethane coating with a coating thickness of 50-100 μm; use an intensity of 20-30 mW / cm 2 The film is then irradiated with ultraviolet light for 30 to 40 minutes for light curing, and then thermally cured at 120 to 140°C for 1 to 2 hours.

[0018] Furthermore, in S11, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methylacrylic acid are mixed at a ratio of 2:1 between epoxy and carboxyl substances.

[0019] Furthermore, in S12, the contents of the components in the photothermal dual-curing epoxy resin material are, by weight, 100 parts of acrylic modified epoxy resin, 20 to 25 parts of epoxy diluent, 20 to 25 parts of free radical active diluent, 1.2 to 1.5 parts of photoinitiator, and 25 to 30 parts of epoxy curing agent.

[0020] Furthermore, in S21, the amount of each component, by weight, is 1-2 parts of nano-silicon dioxide, 15 parts of anhydrous ethanol, 2-3 parts of deionized water, 3-5 parts of ammonia water, and 0.5-0.6 parts of dodecyltriethoxysilane.

[0021] Furthermore, in S22, the mass ratio of polyethylene glycol 2000 to isophorone diisocyanate is (200-220):(330-400).

[0022] Furthermore, in S23, the polyurethane prepolymer and glycidol are mixed in a ratio of 1:1 between the amount of isocyanate group and the amount of hydroxyl substance.

[0023] Furthermore, in S23, the polyurethane prepolymer and hydroxyethyl acrylate are mixed at a ratio of 1:1 between the amount of isocyanate group and the amount of hydroxyl group; after the reaction, 1,1,3,3-tetramethyldisiloxane is added at a ratio of (1.2-1.5) between the amount of vinyl group and the amount of silicon-hydrogen bonded material: 1.

[0024] Furthermore, in S24, epoxy-terminated polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of 1:(4-9); the solid content of the composite polyurethane emulsion is 25-30%.

[0025] Furthermore, in terms of weight, the super hydrophobic polyurethane coating comprises 8 to 15 parts of hydrophobically modified silica and 100 parts of composite polyurethane emulsion.

[0026] Furthermore, in S31, the boron supply agent is mixed with borax and boric acid in a mass ratio of (8-10):1.

[0027] Furthermore, in S31, the rare earth compound consists of lanthanum oxide, lanthanum chloride and lanthanum aluminate, and the mass ratio of the lanthanum oxide, lanthanum chloride and lanthanum aluminate is 1:1:(0.25~0.5).

[0028] Furthermore, the preparation method of the lanthanum aluminate is as follows: aluminum nitrate, potassium hydroxide and water are evenly mixed, and then lanthanum nitrate is added, reacted for 3 to 5 hours, filtered, dried, and then calcined at 900 to 950° C. for 8 to 10 hours to obtain.

[0029] Furthermore, the filler is boron nitride and graphite.

[0030] Furthermore, the penetration catalyst is ammonium chloride and sodium fluoride.

[0031] Furthermore, the mass ratio of the boron supplying agent, the rare earth compound, the filler and the infiltration catalyst is (20-40): (5-10): (50-60): (10-20).

[0032] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention first performs a hardening treatment on the surface of the hydraulic cylinder to improve the hardness and wear resistance of the hydraulic cylinder; on this basis, an organic coating is applied to improve the corrosion resistance of the material.

[0033] When hardening the surface of the hydraulic cylinder, the present invention mixes a boron supply agent, a rare earth compound, graphite, and boron nitride. The rare earth compound increases the diffusion speed and range of the boron element. At the same time, ammonium chloride and sodium fluoride are added as catalysts to assist in improving the penetration ability and penetration speed of boron during the boronizing process. After hardening treatment, the hardness of the metal surface of the hydraulic cylinder is increased and the wear resistance is improved.

[0034] The present invention also provides a coating with corrosion resistance. First, an acrylic modified epoxy resin is synthesized with 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methacrylic acid as raw materials. The acrylic modified epoxy resin contains vinyl and epoxy groups and can be cross-linked by photocuring and thermal curing. The acrylic modified epoxy resin is mixed with an epoxy diluent, a free radical active diluent, a photoinitiator, and an epoxy curing agent to obtain a photothermal dual-curing epoxy resin material. In order to further improve the performance of the corrosion-resistant coating, the present invention uses polyethylene glycol 2000 and isophorone diisocyanate as raw materials to prepare an isocyanate-terminated polyurethane prepolymer; glycidol is used as a capping agent to cap the above polyurethane prepolymer to obtain an epoxy-polyurethane-terminated polyurethane; hydroxyethyl acrylate is used to cap the above polyurethane prepolymer, and the addition reaction of the silicon-hydrogen bond and the carbon-carbon double bond is used, and 1,1,3,3-tetramethyldisiloxane is used as a chain extender to obtain a double-bond-terminated polyurethane containing an organic silicon segment. In addition, the present invention also modifies nano silicon dioxide with dodecyltriethoxysilane to obtain hydrophobically modified silicon dioxide; and mixes hydrophobically modified silicon dioxide, double-bond terminated polyurethane and epoxy terminated polyurethane to obtain a super-hydrophobic polyurethane coating.

[0035] The photothermal dual-curing epoxy resin material and the super-hydrophobic polyurethane coating are sequentially coated on the surface of the hydraulic cylinder treated with surface hardening. The photothermal dual-curing epoxy resin material contains carbon-carbon double bonds and epoxy groups, and can be cured under ultraviolet light and heating conditions. Since the epoxy-terminated polyurethane and the double-bond-terminated polyurethane contain similar segments, the compatibility of the two is very good; during the photocuring process, the double-bond-terminated polyurethane in the super-hydrophobic polyurethane coating will cross-link with the epoxy resin, and in the thermal curing stage, the epoxy-terminated polyurethane in the super-hydrophobic polyurethane coating will cross-link with the epoxy resin; after photothermal dual curing, the two can not only form a three-dimensional cross-linked network structure with the epoxy resin by chemical bonding, but the two different network structures formed can also further form an interpenetrating network with better compatibility in a physical way, which greatly improves the cross-linking density of the surface coating and forms a network coating with a tighter structure, thereby improving the corrosion resistance of the coating. After photothermal curing, the surface polyurethane coating contains hydrophobic silicone segments, so its surface energy is low and its morphology is smooth, so it is subject to less friction during use, which helps to reduce wear during use and extend its service life. The hydrophobically modified silica and the silicone segments synergistically exert a hydrophobic effect, making the coating super hydrophobic.

[0036] In addition, it is necessary to add that the coating order of the photothermal dual-cured epoxy resin material and the super-hydrophobic polyurethane coating on the surface of the hydraulic cylinder cannot be changed. In actual application, if the super-hydrophobic polyurethane coating is applied first and then the photothermal dual-cured epoxy resin material is applied, the performance of the coating is significantly reduced. This is mainly because: First, although the super-hydrophobic polyurethane coating contains two different polyurethanes, a single polyurethane can only be cured once, and the photothermal dual-cured epoxy resin material has significantly better adhesion to metal materials after being cured twice; and because the surface energy of the super-hydrophobic polyurethane coating is low, its adhesion to metal materials is far inferior to that of epoxy resin. Second, the epoxy resin that has not been modified with silicone contains certain hydrophilic groups, so the hydrophobic properties of the coating surface are greatly reduced; the repellency to water and salt spray is poor, and the corrosion resistance is poor. DETAILED DESCRIPTION

[0037] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0038] Materials and sources used in the present invention: epoxy diluent is ethylene glycol diglycidyl ether, free radical active diluent is 1,6-hexanediol diacrylate, photoinitiator is photoinitiator 1173, epoxy curing agent is isophorone diamine, all from Shanghai Aladdin Biochemical Technology Co., Ltd.; nano silicon dioxide (article number XFI03), boron nitride (XFBN03-1), graphite (XF011) are all from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; borax is from Shanghai Yixin Chemical Co., Ltd., with a purity of 95%; the hydraulic cylinder is made of TC6 titanium alloy.

[0039] Embodiment 1: A surface hardening and corrosion resistance process for a hydraulic cylinder, comprising the following steps:

[0040] Step 1:

[0041] S11: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methylacrylic acid are weighed in a ratio of 2:1 between epoxy and carboxyl substances, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane is heated to 80°C, a phase transfer catalyst benzyltriethylammonium chloride, a polymerization inhibitor p-hydroxyanisole, and α-methylacrylic acid are mixed and added to 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, the temperature is raised to 95°C and the reaction is carried out at a constant temperature for 2 hours to obtain an acrylic acid-modified epoxy resin;

[0042] S12: 100 g of acrylic modified epoxy resin, 25 g of epoxy diluent, 25 g of free radical active diluent, 1.3 g of photoinitiator, and 28 g of epoxy curing agent are mixed to obtain a light-heat dual-curing epoxy resin material;

[0043] Step 2:

[0044] S21: 1 g of nano-silica was dispersed in 15 g of anhydrous ethanol, 2 g of deionized water and 3 g of ammonia water were added, 0.5 g of dodecyltriethoxysilane was added under stirring, and the mixture was reacted at 70° C. for 6 h, filtered, washed by centrifugation with anhydrous ethanol, and vacuum dried to obtain hydrophobically modified silica;

[0045] S22: 220 g of polyethylene glycol 2000 and 390 g of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 70° C., and the temperature was kept for reaction for 2 hours to obtain an isocyanate-terminated polyurethane prepolymer;

[0046] S23: The polyurethane prepolymer and glycidol are mixed in a ratio of isocyanate group to hydroxyl substance of 1:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 60°C for reaction for 1 hour, and epoxy-terminated polyurethane is obtained; the polyurethane prepolymer and hydroxyethyl acrylate are mixed in a ratio of isocyanate group to hydroxyl substance of 1:1, dibutyltin dilaurate is used as a catalyst, and p-hydroxyanisole is used as a polymerization inhibitor, the temperature is raised to 60°C for reaction for 1 hour, and 1,1,3,3-tetramethyldisiloxane is added in a ratio of vinyl group to silicon-hydrogen bond substance of 1.5:1 while maintaining the temperature, chloroplatinic acid / isopropanol solution is used as a catalyst, acetone is added during the reaction to adjust the viscosity, the reaction is carried out for 8 hours, and the acetone is removed by reduced pressure distillation to obtain a double-bond-terminated polyurethane;

[0047] S24: epoxy-terminated polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of 1:9, and deionized water is added for emulsification to obtain a composite polyurethane emulsion with a solid content of 30%; 8 g of hydrophobically modified silica is added to 100 g of the composite polyurethane emulsion, and the mixture is mixed to obtain a super-hydrophobic polyurethane coating;

[0048] Step 3:

[0049] S31: 600 g of borax, 75 g of boric acid, 80 g of lanthanum oxide, 80 g of lanthanum chloride, 20 g of lanthanum aluminate, 400 g of boron nitride and 600 g of graphite are vacuum-packed, ball-milled for 4 h at a ball-to-material ratio of 50:1 to mix the powders, 100 g of ammonium chloride and 130 g of sodium fluoride are added as catalysts, vacuum-packed again, and ball-milled for 8 h to obtain a surface hardener;

[0050] S32: Use 10wt% oxalic acid solution to clean, derust and degrease the surface of the hydraulic cylinder, wash with water and dry for standby use; immerse the hydraulic cylinder in a surface hardener and heat it, heat it to 600℃ and keep it for 1h, continue to heat it to 950℃ and keep it for 3h; cool it to 25℃, then quench it at 600℃ and temper it at 220℃ to obtain a surface hardened hydraulic cylinder; wherein, the preparation method of lanthanum aluminate is as follows: mix 1mol aluminum nitrate, 1mol potassium hydroxide and 2L water, add 1mol lanthanum nitrate, stir and react for 5h, filter it out, dry it and calcine it at 930℃ for 10h;

[0051] S33: Apply the photothermal dual-curing epoxy resin material to the surface of the surface-hardened hydraulic cylinder with a coating thickness of 150 μm; then apply the super-hydrophobic polyurethane coating with a coating thickness of 50 μm; use an intensity of 20 mW / cm 2 The film was photocured by irradiating with ultraviolet light for 30 min and thermally cured at 120 °C for 1 h.

[0052] Embodiment 2: A surface hardening and corrosion resistance process for a hydraulic cylinder, comprising the following steps:

[0053] Step 1:

[0054] S11: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methylacrylic acid were weighed in a ratio of 2:1 between epoxy and carboxyl substances, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane was heated to 85°C, a phase transfer catalyst, benzyltriethylammonium chloride, a polymerization inhibitor, and α-methylacrylic acid were mixed and added to 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, the temperature was raised to 95°C and the reaction was carried out at a constant temperature for 2.5 hours to obtain an acrylic acid-modified epoxy resin;

[0055] S12: 100 g of acrylic modified epoxy resin, 25 g of epoxy diluent, 25 g of free radical active diluent, 1.3 g of photoinitiator, and 28 g of epoxy curing agent are mixed to obtain a light-heat dual-curing epoxy resin material;

[0056] Step 2:

[0057] S21: 1 g of nano-silica was dispersed in 15 g of anhydrous ethanol, 2 g of deionized water and 3 g of ammonia water were added, 0.5 g of dodecyltriethoxysilane was added under stirring, and the mixture was reacted at 75° C. for 7 h, filtered, washed by centrifugation with anhydrous ethanol, and vacuum dried to obtain hydrophobically modified silica;

[0058] S22: 220 g of polyethylene glycol 2000 and 390 g of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 75° C., and the temperature was kept for reaction for 2.5 hours to obtain an isocyanate-terminated polyurethane prepolymer;

[0059] S23: The polyurethane prepolymer and glycidol are mixed in a ratio of isocyanate group to hydroxyl substance of 1:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 65°C for reaction for 1.5 hours, and epoxy-terminated polyurethane is obtained; the polyurethane prepolymer and hydroxyethyl acrylate are mixed in a ratio of isocyanate group to hydroxyl substance of 1:1, dibutyltin dilaurate is used as a catalyst, and p-hydroxyanisole is used as a polymerization inhibitor, the temperature is raised to 65°C for reaction for 1.5 hours, and 1,1,3,3-tetramethyldisiloxane is added in a ratio of vinyl group to silicon-hydrogen bond substance of 1.5:1 while maintaining the temperature, chloroplatinic acid / isopropanol solution is used as a catalyst, acetone is added during the reaction to adjust the viscosity, the reaction is carried out for 9 hours, and the acetone is removed by vacuum distillation to obtain a double-bond-terminated polyurethane;

[0060] S24: epoxy-terminated polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of 1:9, and deionized water is added for emulsification to obtain a composite polyurethane emulsion with a solid content of 30%; 12 g of hydrophobically modified silica is added to 100 g of the composite polyurethane emulsion, and the mixture is mixed to obtain a super-hydrophobic polyurethane coating;

[0061] Step 3:

[0062] S31: 600 g of borax, 75 g of boric acid, 80 g of lanthanum oxide, 80 g of lanthanum chloride, 20 g of lanthanum aluminate, 400 g of boron nitride and 600 g of graphite are vacuum-packed, ball-milled for 4 h at a ball-to-material ratio of 50:1 to mix the powders, 100 g of ammonium chloride and 130 g of sodium fluoride are added as catalysts, vacuum-packed again, and ball-milled for 8 h to obtain a surface hardener;

[0063] S32: Use 10wt% oxalic acid solution to clean, derust and degrease the surface of the hydraulic cylinder, wash with water and dry for later use; immerse the hydraulic cylinder in a surface hardener and heat it, heat it to 640℃ and keep it for 1.5h, continue to heat it to 970℃ and keep it for 4h; cool it to 30℃, then quench it at 625℃ and temper it at 230℃ to obtain a surface hardened hydraulic cylinder; wherein, the preparation method of lanthanum aluminate is as follows: mix 1mol aluminum nitrate, 1mol potassium hydroxide and 2L water, add 1mol lanthanum nitrate, stir and react for 5h, filter it out, dry it and calcine it at 930℃ for 10h;

[0064] S33: Apply the photothermal dual-curing epoxy resin material to the surface of the surface-hardened hydraulic cylinder with a coating thickness of 150 μm; then apply the super-hydrophobic polyurethane coating with a coating thickness of 50 μm; use an intensity of 25 mW / cm 2 The film was photocured by irradiating with ultraviolet light for 35 minutes and thermally cured at 130°C for 1.5 hours.

[0065] Embodiment 3: A surface hardening and corrosion resistance process for a hydraulic cylinder, comprising the following steps:

[0066] Step 1:

[0067] S11: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methylacrylic acid are weighed in a ratio of 2:1 between epoxy and carboxyl substances, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane is heated to 90°C, a phase transfer catalyst benzyltriethylammonium chloride, a polymerization inhibitor p-hydroxyanisole, and α-methylacrylic acid are mixed and added to 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, the temperature is raised to 100°C and the reaction is carried out at a constant temperature for 3 hours to obtain an acrylic acid-modified epoxy resin;

[0068] S12: 100 g of acrylic modified epoxy resin, 25 g of epoxy diluent, 25 g of free radical active diluent, 1.3 g of photoinitiator, and 28 g of epoxy curing agent are mixed to obtain a light-heat dual-curing epoxy resin material;

[0069] Step 2:

[0070] S21: 1 g of nano-silica was dispersed in 15 g of anhydrous ethanol, 2 g of deionized water and 3 g of ammonia water were added, 0.5 g of dodecyltriethoxysilane was added under stirring, and the mixture was reacted at 80° C. for 8 h, filtered, washed by centrifugation with anhydrous ethanol, and vacuum dried to obtain hydrophobically modified silica;

[0071] S22: 220 g of polyethylene glycol 2000 and 390 g of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 80° C., and the temperature was kept for reaction for 3 hours to obtain an isocyanate-terminated polyurethane prepolymer;

[0072] S23: The polyurethane prepolymer and glycidol are mixed in a ratio of isocyanate group to hydroxyl substance of 1:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 70°C for reaction for 2 hours, and epoxy-terminated polyurethane is obtained; the polyurethane prepolymer and hydroxyethyl acrylate are mixed in a ratio of isocyanate group to hydroxyl substance of 1:1, dibutyltin dilaurate is used as a catalyst, and p-hydroxyanisole is used as a polymerization inhibitor, the temperature is raised to 70°C for reaction for 2 hours, and 1,1,3,3-tetramethyldisiloxane is added in a ratio of vinyl group to silicon-hydrogen bond substance of 1.5:1 while maintaining the temperature, chloroplatinic acid / isopropanol solution is used as a catalyst, acetone is added during the reaction to adjust the viscosity, the reaction is carried out for 10 hours, and the acetone is removed by vacuum distillation to obtain a double-bond-terminated polyurethane;

[0073] S24: epoxy-terminated polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of 1:9, and deionized water is added for emulsification to obtain a composite polyurethane emulsion with a solid content of 30%; 15 g of hydrophobically modified silica is added to 100 g of the composite polyurethane emulsion, and the mixture is mixed to obtain a super-hydrophobic polyurethane coating;

[0074] Step 3:

[0075] S31: 600 g of borax, 75 g of boric acid, 80 g of lanthanum oxide, 80 g of lanthanum chloride, 20 g of lanthanum aluminate, 400 g of boron nitride and 600 g of graphite are vacuum-packed, ball-milled for 4 h at a ball-to-material ratio of 50:1 to mix the powders, 100 g of ammonium chloride and 130 g of sodium fluoride are added as catalysts, vacuum-packed again, and ball-milled for 8 h to obtain a surface hardener;

[0076] S32: Use 10wt% oxalic acid solution to clean, derust and degrease the surface of the hydraulic cylinder, wash with water and dry for standby use; immerse the hydraulic cylinder in a surface hardener and heat it, heat it to 650℃ and keep it for 2h, continue to heat it to 980℃ and keep it for 5h; cool it to 30℃, then quench it at 650℃ and temper it at 240℃ to obtain a surface hardened hydraulic cylinder; wherein, the preparation method of lanthanum aluminate is as follows: mix 1mol aluminum nitrate, 1mol potassium hydroxide and 2L water, add 1mol lanthanum nitrate, stir and react for 5h, filter it out, dry it and calcine it at 930℃ for 10h;

[0077] S33: Apply the photothermal dual-curing epoxy resin material to the surface of the surface-hardened hydraulic cylinder with a coating thickness of 150 μm; then apply the super-hydrophobic polyurethane coating with a coating thickness of 50 μm; use an intensity of 30 mW / cm 2 The film was photocured by irradiating with ultraviolet light for 40 min and thermally cured at 140 °C for 2 h.

[0078] Comparative Example 1: No hardening treatment was performed, and the other parameters were the same as those of Example 1.

[0079] Step 1:

[0080] S11: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methylacrylic acid are weighed in a ratio of 2:1 between epoxy and carboxyl substances, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane is heated to 80°C, a phase transfer catalyst benzyltriethylammonium chloride, a polymerization inhibitor p-hydroxyanisole, and α-methylacrylic acid are mixed and added to 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, the temperature is raised to 95°C and the reaction is carried out at a constant temperature for 2 hours to obtain an acrylic acid-modified epoxy resin;

[0081] S12: 100 g of acrylic modified epoxy resin, 25 g of epoxy diluent, 25 g of free radical active diluent, 1.3 g of photoinitiator, and 28 g of epoxy curing agent are mixed to obtain a light-heat dual-curing epoxy resin material;

[0082] Step 2:

[0083] S21: 1 g of nano-silica was dispersed in 15 g of anhydrous ethanol, 2 g of deionized water and 3 g of ammonia water were added, 0.5 g of dodecyltriethoxysilane was added under stirring, and the mixture was reacted at 70° C. for 6 h, filtered, washed by centrifugation with anhydrous ethanol, and vacuum dried to obtain hydrophobically modified silica;

[0084] S22: 220 g of polyethylene glycol 2000 and 390 g of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 70° C., and the temperature was kept for reaction for 2 hours to obtain an isocyanate-terminated polyurethane prepolymer;

[0085] S23: The polyurethane prepolymer and glycidol are mixed in a ratio of isocyanate group to hydroxyl substance of 1:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 60°C for reaction for 1 hour, and epoxy-terminated polyurethane is obtained; the polyurethane prepolymer and hydroxyethyl acrylate are mixed in a ratio of isocyanate group to hydroxyl substance of 1:1, dibutyltin dilaurate is used as a catalyst, and p-hydroxyanisole is used as a polymerization inhibitor, the temperature is raised to 60°C for reaction for 1 hour, and 1,1,3,3-tetramethyldisiloxane is added in a ratio of vinyl group to silicon-hydrogen bond substance of 1.5:1 while maintaining the temperature, chloroplatinic acid / isopropanol solution is used as a catalyst, acetone is added during the reaction to adjust the viscosity, the reaction is carried out for 8 hours, and the acetone is removed by reduced pressure distillation to obtain a double-bond-terminated polyurethane;

[0086] S24: epoxy-terminated polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of 1:9, and deionized water is added for emulsification to obtain a composite polyurethane emulsion with a solid content of 30%; 8 g of hydrophobically modified silica is added to 100 g of the composite polyurethane emulsion, and the mixture is mixed to obtain a super-hydrophobic polyurethane coating;

[0087] Step 3:

[0088] The surface of the hydraulic cylinder was cleaned, derusted and degreased with 10wt% oxalic acid solution, washed with water and dried for later use; the photothermal dual-curing epoxy resin was applied to the surface of the hydraulic cylinder with a coating thickness of 150μm; then a super-hydrophobic polyurethane coating was applied with a coating thickness of 50μm; an intensity of 20mW / cm 2 The film was photocured by irradiating with ultraviolet light for 30 min and thermally cured at 120 °C for 1 h.

[0089] Comparative Example 2: Only the hydrophobically modified silica and the double-bond terminated polyurethane were mixed to prepare a super hydrophobic polyurethane coating, and the other parameters were the same as those in Example 2.

[0090] Step 1:

[0091] S11: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methylacrylic acid were weighed in a ratio of 2:1 between epoxy and carboxyl substances, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane was heated to 85°C, a phase transfer catalyst, benzyltriethylammonium chloride, a polymerization inhibitor, and α-methylacrylic acid were mixed and added to 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, the temperature was raised to 95°C and the reaction was carried out at a constant temperature for 2.5 hours to obtain an acrylic acid-modified epoxy resin;

[0092] S12: 100 g of acrylic modified epoxy resin, 25 g of epoxy diluent, 25 g of free radical active diluent, 1.3 g of photoinitiator, and 28 g of epoxy curing agent are mixed to obtain a light-heat dual-curing epoxy resin material;

[0093] Step 2:

[0094] S21: 1 g of nano-silica was dispersed in 15 g of anhydrous ethanol, 2 g of deionized water and 3 g of ammonia water were added, 0.5 g of dodecyltriethoxysilane was added under stirring, and the mixture was reacted at 75° C. for 7 h, filtered, washed by centrifugation with anhydrous ethanol, and vacuum dried to obtain hydrophobically modified silica;

[0095] S22: 220 g of polyethylene glycol 2000 and 390 g of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 75° C., and the temperature was kept for reaction for 2.5 hours to obtain an isocyanate-terminated polyurethane prepolymer;

[0096] S23: a polyurethane prepolymer and hydroxyethyl acrylate are mixed in a ratio of isocyanate group to hydroxyl group of 1:1, dibutyltin dilaurate is used as a catalyst, p-hydroxyanisole is used as an inhibitor, the temperature is raised to 65°C for reaction for 1.5 hours, 1,1,3,3-tetramethyldisiloxane is added in a ratio of vinyl group to silicon-hydrogen bond of 1.5:1, chloroplatinic acid / isopropanol solution is used as a catalyst, acetone is added during the reaction to adjust the viscosity, the reaction is carried out for 9 hours, and the acetone is removed by vacuum distillation to obtain a double-bond terminated polyurethane;

[0097] S24: adding deionized water to the double-bond terminated polyurethane to emulsify and obtain a polyurethane emulsion with a solid content of 30%; adding 12 g of hydrophobically modified silica to 100 g of the polyurethane emulsion to obtain a super hydrophobic polyurethane coating;

[0098] Step 3:

[0099] S31: 600 g of borax, 75 g of boric acid, 80 g of lanthanum oxide, 80 g of lanthanum chloride, 20 g of lanthanum aluminate, 400 g of boron nitride and 600 g of graphite are vacuum-packed, ball-milled for 4 h at a ball-to-material ratio of 50:1 to mix the powders, 100 g of ammonium chloride and 130 g of sodium fluoride are added as catalysts, vacuum-packed again, and ball-milled for 8 h to obtain a surface hardener;

[0100] S32: Use 10wt% oxalic acid solution to clean, derust and degrease the surface of the hydraulic cylinder, wash with water and dry for later use; immerse the hydraulic cylinder in a surface hardener and heat it, heat it to 640℃ and keep it for 1.5h, continue to heat it to 970℃ and keep it for 4h; cool it to 30℃, then quench it at 625℃ and temper it at 230℃ to obtain a surface hardened hydraulic cylinder; wherein, the preparation method of lanthanum aluminate is as follows: mix 1mol aluminum nitrate, 1mol potassium hydroxide and 2L water, add 1mol lanthanum nitrate, stir and react for 5h, filter it out, dry it and calcine it at 930℃ for 10h;

[0101] S33: Apply the photothermal dual-curing epoxy resin material to the surface of the surface-hardened hydraulic cylinder with a coating thickness of 150 μm; then apply the super-hydrophobic polyurethane coating with a coating thickness of 50 μm; use an intensity of 25 mW / cm 2 The film was photocured by irradiating with ultraviolet light for 35 minutes and thermally cured at 130°C for 1.5 hours.

[0102] Comparative Example 3: The super-hydrophobic polyurethane coating was first applied, and then the photothermal dual-curing epoxy resin material was applied. The other parameters were the same as those in Example 3.

[0103] Step 1:

[0104] S11: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methylacrylic acid are weighed in a ratio of 2:1 between epoxy and carboxyl substances, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane is heated to 90°C, a phase transfer catalyst benzyltriethylammonium chloride, a polymerization inhibitor p-hydroxyanisole, and α-methylacrylic acid are mixed and added to 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, the temperature is raised to 100°C and the reaction is carried out at a constant temperature for 3 hours to obtain an acrylic acid-modified epoxy resin;

[0105] S12: 100 g of acrylic modified epoxy resin, 25 g of epoxy diluent, 25 g of free radical active diluent, 1.3 g of photoinitiator, and 28 g of epoxy curing agent are mixed to obtain a light-heat dual-curing epoxy resin material;

[0106] Step 2:

[0107] S21: 1 g of nano-silica was dispersed in 15 g of anhydrous ethanol, 2 g of deionized water and 3 g of ammonia water were added, 0.5 g of dodecyltriethoxysilane was added under stirring, and the mixture was reacted at 80° C. for 8 h, filtered, washed by centrifugation with anhydrous ethanol, and vacuum dried to obtain hydrophobically modified silica;

[0108] S22: 220 g of polyethylene glycol 2000 and 390 g of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 80° C., and the temperature was kept for reaction for 3 hours to obtain an isocyanate-terminated polyurethane prepolymer;

[0109] S23: The polyurethane prepolymer and glycidol are mixed in a ratio of isocyanate group to hydroxyl substance of 1:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 70°C for reaction for 2 hours, and epoxy-terminated polyurethane is obtained; the polyurethane prepolymer and hydroxyethyl acrylate are mixed in a ratio of isocyanate group to hydroxyl substance of 1:1, dibutyltin dilaurate is used as a catalyst, and p-hydroxyanisole is used as a polymerization inhibitor, the temperature is raised to 70°C for reaction for 2 hours, and 1,1,3,3-tetramethyldisiloxane is added in a ratio of vinyl group to silicon-hydrogen bond substance of 1.5:1 while maintaining the temperature, chloroplatinic acid / isopropanol solution is used as a catalyst, acetone is added during the reaction to adjust the viscosity, the reaction is carried out for 10 hours, and the acetone is removed by vacuum distillation to obtain a double-bond-terminated polyurethane;

[0110] S24: epoxy-terminated polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of 1:9, and deionized water is added for emulsification to obtain a composite polyurethane emulsion with a solid content of 30%; 15 g of hydrophobically modified silica is added to 100 g of the composite polyurethane emulsion, and the mixture is mixed to obtain a super-hydrophobic polyurethane coating;

[0111] Step 3:

[0112] S31: 600 g of borax, 75 g of boric acid, 80 g of lanthanum oxide, 80 g of lanthanum chloride, 20 g of lanthanum aluminate, 400 g of boron nitride and 600 g of graphite are vacuum-packed, ball-milled for 4 h at a ball-to-material ratio of 50:1 to mix the powders, 100 g of ammonium chloride and 130 g of sodium fluoride are added as catalysts, vacuum-packed again, and ball-milled for 8 h to obtain a surface hardener;

[0113] S32: Use 10wt% oxalic acid solution to clean, derust and degrease the surface of the hydraulic cylinder, wash with water and dry for standby use; immerse the hydraulic cylinder in a surface hardener and heat it, heat it to 650℃ and keep it for 2h, continue to heat it to 980℃ and keep it for 5h; cool it to 30℃, then quench it at 650℃ and temper it at 240℃ to obtain a surface hardened hydraulic cylinder; wherein, the preparation method of lanthanum aluminate is as follows: mix 1mol aluminum nitrate, 1mol potassium hydroxide and 2L water, add 1mol lanthanum nitrate, stir and react for 5h, filter it out, dry it and calcine it at 930℃ for 10h;

[0114] S33: Apply super hydrophobic polyurethane coating to the surface of the surface hardened hydraulic cylinder with a coating thickness of 50 μm; then apply photothermal dual-curing epoxy resin coating with a coating thickness of 150 μm; use an intensity of 30 mW / cm 2 The film was photocured by irradiating with ultraviolet light for 40 min and thermally cured at 140 °C for 2 h.

[0115] Experiment: After the surface of the TC6 titanium alloy plate was treated by the processes in Examples 1 to 3 and Comparative Examples 1 to 3, performance tests were performed respectively. The test methods are as follows:

[0116] Wear resistance: The wear resistance test was carried out on an M-200 wear tester at room temperature. The friction pair material was GCr15, with a hardness of 62HRC. The upper and lower wheel speeds were 200r / min and 180r / min respectively. A weight of 30kg was loaded. The weight was weighed after 200 minutes, and the mass loss was recorded.

[0117] Corrosion resistance: A neutral solution of sodium chloride with a mass concentration of 5% was selected as the salt spray medium. The samples were placed in a salt spray chamber. The temperature in the salt spray chamber was maintained at 25±1°C. The changes in the coating morphology were observed after 60 hours.

[0118] Surface hydrophobicity: tested using static water drop contact angle.

[0119] Adhesion performance test: refer to standard GB 1720 / 79 (88), use circle method to test adhesion level 1~7, the best adhesion is level 1; the worst adhesion is level 7.

[0120]

[0121] Conclusion: The data of Examples 1 to 3 show that the process of the present invention can effectively improve the surface hardness and corrosion resistance of the hydraulic cylinder. The data of Example 1 and Comparative Example 1 show that the wear resistance of the hardened hydraulic cylinder surface is stronger; the data of Example 2 and Comparative Example 2 show that after adding epoxy-terminated polyurethane, the adhesion of the coating is stronger; the data of Example 3 and Comparative Example 3 show that the coating scheme of the present invention can effectively improve the corrosion resistance of the coating after coating the surface of the hydraulic cylinder, and the cured coating has good adhesion.

[0122] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A surface hardening and corrosion-resistant process for a hydraulic cylinder, characterized in that: The following steps are involved: Step 1: The surface of the hydraulic cylinder is derusted and degreased with oxalic acid solution, washed and dried, and then placed in a surface hardener for heating and infiltration, heated to 600-650°C and kept for 1-2 hours, and then continued to heat to 950-980°C and kept for 3-5 hours; cooled to 25-30°C, and then quenched at 600-650°C and tempered at 200-220°C to obtain a surface hardened hydraulic cylinder; The preparation method of the surface hardener is: The boron supply agent, the rare earth compound, the filler, and the infiltration catalyst are mixed in a mass ratio of (20-40): (5-10): (50-60): (10-20) to obtain a surface hardener; Step 2: The photo-thermal dual-curing epoxy resin material is coated on the surface of the surface-hardened hydraulic cylinder, and then a super-hydrophobic polyurethane coating is coated, and a corrosion-resistant coating is obtained through photo-curing and thermal curing; The preparation method of the photothermal dual-curing epoxy resin material comprises: heating 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane to 80-90° C., mixing a phase transfer catalyst benzyltriethylammonium chloride, a polymerization inhibitor p-hydroxyanisole, and α-methylacrylic acid, and adding the mixture to 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, heating the mixture to 95-100° C. and reacting the mixture at a constant temperature for 2-3 hours to obtain an acrylic acid-modified epoxy resin; mixing the acrylic acid-modified epoxy resin, an epoxy diluent, a free radical active diluent, a photoinitiator, and an epoxy curing agent to obtain a photothermal dual-curing epoxy resin material; The preparation method of the super hydrophobic polyurethane coating comprises the following steps: S1: Disperse 1-2 parts of nano-silica in 15 parts of anhydrous ethanol by weight, add 2-3 parts of deionized water and 3-5 parts of ammonia water, stir and add 0.5-0.6 parts of dodecyltriethoxysilane, react at 70-80°C for 6-8h, filter and wash by centrifugation with anhydrous ethanol, and vacuum dry to obtain hydrophobically modified silica; S2: Mix polyethylene glycol 2000 and isophorone diisocyanate in a mass ratio of (200-220): (330-400), use dibutyltin dilaurate as a catalyst, heat to 70-80°C, and keep the temperature for reaction for 2-3 hours to obtain an isocyanate-terminated polyurethane prepolymer; S3: The polyurethane prepolymer and glycidol are mixed in a ratio of isocyanate group to hydroxyl group of 1:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 60-70°C for reaction for 1-2 hours, and epoxy-terminated polyurethane is obtained; the polyurethane prepolymer and hydroxyethyl acrylate are mixed in a ratio of isocyanate group to hydroxyl group of 1:1, dibutyltin dilaurate is used as a catalyst, and p-hydroxyanisole is used as a polymerization inhibitor, the temperature is raised to 60-70°C for reaction for 1-2 hours, and 1,1,3,3-tetramethyldisiloxane is added in a ratio of vinyl group to silicon-hydrogen bond (1.2-1.5):1 while keeping warm, chloroplatinic acid / isopropanol solution is used as a catalyst, acetone is added during the reaction to adjust the viscosity, the reaction is carried out for 8-10 hours, and the acetone is removed by vacuum distillation to obtain a double-bond-terminated polyurethane; S4: Epoxy-terminated polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of 1:(4-9), and deionized water is added for emulsification to obtain a composite polyurethane emulsion with a solid content of 25-30%; 8-15 parts by weight of hydrophobically modified silica are added to 100 parts of the composite polyurethane emulsion, and the mixture is mixed to obtain a super-hydrophobic polyurethane coating.

2. The surface hardening and corrosion resistance process of a hydraulic cylinder according to claim 1, characterized in that: The boron supply agent is obtained by mixing borax and boric acid in a mass ratio of (8-10):1; the rare earth compound is obtained by mixing lanthanum oxide, lanthanum chloride and lanthanum aluminate in a mass ratio of 1:1:(0.25-0.5); the filler is boron nitride and graphite; and the catalyst is ammonium chloride and sodium fluoride.

3. The surface hardening and corrosion resistance process of a hydraulic cylinder according to claim 2, characterized in that: The preparation method of lanthanum aluminate is as follows: after aluminum nitrate, potassium hydroxide and water are uniformly mixed, lanthanum nitrate is added, reacted for 3-5 hours, filtered, dried, and then calcined at 900-950° C. for 8-10 hours to obtain the lanthanum aluminate, wherein the molar ratio of aluminum nitrate, potassium hydroxide and lanthanum nitrate is 1:1:

1.

4. The surface hardening and corrosion resistance process of a hydraulic cylinder according to claim 1, characterized in that: In 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methylacrylic acid, the ratio of the amount of epoxy group to the amount of hydroxyl group is 1:

1.

5. The surface hardening and corrosion-resistant process of a hydraulic cylinder according to claim 1, characterized in that: The content of each component in the light-heat dual-curing epoxy resin material, by weight, is 100 parts of acrylic modified epoxy resin, 20-25 parts of epoxy diluent, 20-25 parts of free radical active diluent, 1.2-1.5 parts of photoinitiator, and 25-30 parts of epoxy curing agent.

6. The surface hardening and corrosion resistance process of a hydraulic cylinder according to claim 1, characterized in that: In step 2, the coating thickness of the photothermal dual-curing epoxy resin material is 150-200 μm; the coating thickness of the super-hydrophobic polyurethane coating is 50-100 μm.

7. The surface hardening and corrosion resistance process of a hydraulic cylinder according to claim 1, characterized in that: In step 2, the light curing intensity is 20~30mW / cm 2 UV irradiation for 30~40min; thermal curing temperature is 120~140℃, and the time is 1~2h.

Citation Information

Patent Citations

  • Method for preparing dually cured coating

    CN104497804A

  • Hydrophobic biomass fibers and preparation method thereof

    CN109023951A